Water bucket colour preferences in horses - Yildirim, Fatih; Yildiz, Ahmet (Austral Journal of Veterinary Sciences, 2020)
There is a general agreement that horses have dichromatic colour vision with similar capabilities to those of human beings with red-green colour deficiencies. However, whether colour perception has an impact on equine preference for drinking water and how pronounced the colour stimulus might be for horses is still unknown. This study aimed to investigate the preference of horses for different coloured buckets (red, light green, yellow, green, light blue, turquoise) with different tones, in terms of lightness and darkness, measured by the amount of water consumed from each of them in an outdoor arena. Three Thoroughbred and 3 Haflinger horses were used in the study, and data were collected between 09:00 - 16:00 h. The results showed that the average water consumption during this period can reach up to 25.74 L (at an average environmental temperature of 27.35 °C), and significantly more water had been consumed from the turquoise-coloured bucket than from the other colours. It was also observed that the light toned colours (turquoise, light blue) were preferred to dark ones (green, yellow, red). It is suggested to use water buckets that are turquoise and light blue. Further studies are needed to better understand the relationship between water consumption and colour vision.